Postglacial relative sea level change and glacier activity in the early and late Holocene: Wahlenbergfjorden, Nordaustlandet, Svalbard - Schomacker, Anders; Farnsworth, Wesley Randall; Ingólfsson, Ólafur; Allaart, Lis; Håkansson, Lena; Retelle, Michael; Marie-Louise, Siggaard-Andersen; Korsgaard, Niels J.; Rouillard, Alexandra; Kjellman, Sofia Elisabeth (Scientific Reports, 2019)
Published article, available at: https://doi.org/10.1038/s41598-019-43342-z Sediment cores from Kløverbladvatna, a threshold lake in Wahlenbergfjorden, Nordaustlandet, Svalbard were used to reconstruct Holocene glacier fluctuations. Meltwater from Etonbreen spills over a threshold to the lake, only when the glacier is significantly larger than at present. Lithological logging, loss-on-ignition, ITRAX scanning and radiocarbon dating of the cores show that Kløverbladvatna became isolated from Wahlenbergfjorden c. 5.4 cal. kyr BP due to glacioisostatic rebound. During the Late Holocene, laminated clayey gyttja from lacustrine organic production and surface runoff from the catchment accumulated in the lake. The lacustrine sedimentary record suggests that meltwater only spilled over the threshold at the peak of the surge of Etonbreen in AD 1938. Hence, we suggest that this was the largest extent of Etonbreen in the (mid-late) Holocene. In Palanderbukta, a tributary fjord to Wahlenbergfjorden, raised beaches were surveyed and organic material collected to determine the age of the beaches and reconstruct postglacial relative sea level change. The age of the postglacial raised beaches ranges from 10.7 cal. kyr BP at 50 m a.s.l. to 3.13 cal. kyr BP at 2 m a.s.l. The reconstructed postglacial relative sea level curve adds valuable spatial and chronological data to the relative sea level record of Nordaustlandet.